Robot-assisted minimally invasive distal pancreatectomy is superior to the laparoscopic technique - Daouadi, Mustapha; Zureikat, Amer H; Zenati, Mazen S; Choudry, Haroon; Tsung, Alan; Bartlett, David L; Hughes, Steven J; Lee, Ken K; Moser, A James; Zeh, Herbert J (Annals of surgery, 2013)
Laparoscopic distal pancreatectomy (LDP) reduces postoperative morbidity, hospital stay, and recovery as compared with open distal pancreatectomy. Technical limitations of laparoscopic surgery may limit patient eligibility and require conversion to open or hand-assisted surgery to maintain patient safety. We hypothesized that robot-assisted distal pancreatectomy (RADP) was superior to LDP as a result of improved surgical manipulation and visualization, potentially expanding the indications for minimally invasive pancreatectomy. We performed a retrospective analysis of all minimally invasive distal pancreatectomies at University of Pittsburgh Medical Center between January 2004 and February 2011. We compared the perioperative outcomes, 90-day morbidity and mortality of our first 30 RADPs to 94 consecutive historical control LDPs. Patients undergoing RADP and LDP demonstrated equivalent age, sex, race, American Society of Anesthesiologists' score, and tumor size. Postoperative length of hospital stay and rates of pancreatic fistula, blood transfusion, and readmission were not statistically different. Patients in the RADP group did not require conversion to open surgery unlike the LDP group (16%, P < 0.05) and had reduced risk of excessive blood loss. There were more pancreatic ductal adenocarcinomas approached robotically (43%) than laparoscopically (15%) (P < 0.05). Oncological outcomes in these cases were superior for the robotic-assisted group with higher rates of margin negative resection and improved lymph node yield for both benign and malignant lesions (P < 0.0001). RADPs were equivalent to LDPs in nearly all measures of outcome and safety but significantly reduced the risk of conversion to open resection, despite a statistically greater probability of malignancy in the robotic cohort. We concluded that robotic assistance may broaden indications for minimally invasive pancreatectomy.